2004
DOI: 10.1016/j.jasms.2004.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Bimetallic silver-gold clusters by matrix-assisted laser desorption/ionization

Abstract: Pure gold clusters (Au n ϩ ) were produced up to the cluster size of n ϭ 100 by matrix-assisted laser desorption/ionization (MALDI). The mass spectrum of the resulting clusters showed alteration in the ion intensity at odd-even clusters size. On the other hand, intensity drops at cluster size predicted by the jellium model theory was also observed. Positively and negatively charged bimetallic silver-gold clusters were produced under MALDI conditions from the mixture of HAuCl 4 /silver trifluoroacetate and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
11
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 34 publications
3
11
0
Order By: Relevance
“…Clusters of monoisotopic elements provide simple spectra with many monoisotopic peaks covering the mass range of interest with regular mass spacing. In this work, we discuss the calibration of mass spectra by clusters of red phosphorus, which is already established in our laboratory [6,[10][11][12][13][14][15][16], and compare it with calibration by gold clusters generated directly on the target by laser desorption ionization (LDI)-MS of various materials, including gold foil [17], various types of gold nanoparticles (AuNPs), chloroauric acid (HAuCl 4 ), a mixture of 2-(4-hydroxyphenylazo) benzoic acid and HAuCl 4 [18], and polyvinylpyrrolidone-stabilized AuNPs [19]. Gold clusters provide simple and fast determination of accurate mass compared with common calibration standards, such as peptides or proteins.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clusters of monoisotopic elements provide simple spectra with many monoisotopic peaks covering the mass range of interest with regular mass spacing. In this work, we discuss the calibration of mass spectra by clusters of red phosphorus, which is already established in our laboratory [6,[10][11][12][13][14][15][16], and compare it with calibration by gold clusters generated directly on the target by laser desorption ionization (LDI)-MS of various materials, including gold foil [17], various types of gold nanoparticles (AuNPs), chloroauric acid (HAuCl 4 ), a mixture of 2-(4-hydroxyphenylazo) benzoic acid and HAuCl 4 [18], and polyvinylpyrrolidone-stabilized AuNPs [19]. Gold clusters provide simple and fast determination of accurate mass compared with common calibration standards, such as peptides or proteins.…”
Section: Introductionmentioning
confidence: 99%
“…Kéki et al described the generation of positively charged gold clusters up to m/z 18,000 in positive reflectron ion mode, but they identified only single isotopic peaks for clusters with masses up to 3000 Da and reported the presence of hydride-type ions like Au n H + [18]. Furthermore, they did not provide a detailed evaluation and statistical analysis.…”
Section: Introductionmentioning
confidence: 99%
“…The formation of gaseous metal anions by decomposition of a salt in which the metal is initially present in cationic form is a rare chemical process. [6] Metal anions emerging from the linear quadrupole region of the mass spectrometer according to the procedure described bear lower kinetic energies than the anions generated by other high-energy processes. [7][8][9][10][11][12][13] Most previously described alkali anion generating methods require sophisticated instrumentation therefore not amenable to simple bench-top applications.…”
mentioning
confidence: 99%
“…[5] Three studies of anionic photoelectron spectroscopy (PES) on Au m Ag n À clusters have been reported very recently. [6][7][8] Theoretical studies of neutral gold-silver clusters have been reported recently by Bonacic-Koutecky et al [2,9,10] and Kim and co-workers, [11] who investigated the geometric and electronic structures of such bimetallic clusters. On the basis of density functional theory (DFT) calculations, they noted two effects in bimetallic clusters: 1) stable structures of small bimetallic clusters tend to remain planar; 2) the difference in electronegativity results in charge transfer (CT) from silver to gold atoms, resulting in a partial positive charge residing on the silver atoms.…”
Section: Introductionmentioning
confidence: 96%